2020
DOI: 10.1097/jte.0000000000000164
|View full text |Cite
|
Sign up to set email alerts
|

The Need for a Leadership Competency Framework for Physical Therapists: A Perspective in Action

Abstract: Background and Purpose. “Leadership at all levels” has been identified as one of the 12 critical issues facing organizations around the world. The American Physical Therapy Association Vision calls physical therapists “to lead” efforts to transform society. Leadership competencies essential for practice recently have been identified. These competencies illustrate how physical therapists independent of professional role and position can support achievement of the Quadruple Aim. The profession has ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…In contrast, the physical therapists in this study recognized the applicability of clinical skills directly to the practice of leadership. This finding supports current calls to include leadership as a component of the physical therapist professional role identity (Desveaux and Verrier, 2014; Green-Wilson et al , 2022; McGowan, 2017; McGowan and Stokes, 2015, 2017; Rasmussen-Barr et al , 2019; Sebelski et al , 2020; Tschoepe et al , 2021). Despite increasing support in the research, the recent core competencies of PT practice released by the American Council on Academic Physical Therapy and the American Physical Therapy Association fail to include leadership (Knox et al , 2022).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, the physical therapists in this study recognized the applicability of clinical skills directly to the practice of leadership. This finding supports current calls to include leadership as a component of the physical therapist professional role identity (Desveaux and Verrier, 2014; Green-Wilson et al , 2022; McGowan, 2017; McGowan and Stokes, 2015, 2017; Rasmussen-Barr et al , 2019; Sebelski et al , 2020; Tschoepe et al , 2021). Despite increasing support in the research, the recent core competencies of PT practice released by the American Council on Academic Physical Therapy and the American Physical Therapy Association fail to include leadership (Knox et al , 2022).…”
Section: Discussionsupporting
confidence: 83%
“…This finding conflicts with the majority of literature on clinicians turned managers/leaders from other health-care professions and exposes a paradox in the existing PT leadership literature (Masoumi, 2019; Shams et al , 2019; Spehar et al , 2012). The existing body of research in PT leadership often frames leadership/management skills as separate from other skills in the physical therapist’s repertoire (Green-Wilson, 2011; Lopopolo et al , 2004; McGowan et al , 2016; Schafer et al , 2007; Silberman et al , 2020; Tschoepe et al , 2021). In contrast, the physical therapists in this study recognized the applicability of clinical skills directly to the practice of leadership.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recent studies identified and defined personal leadership behaviors for DPT students 3 and developed a framework, the Leadership Competency Framework for Physical Therapists (LCF-PT). 9 A Delphi study recruited experts in leadership ( n = 14) who ranked the level of importance of 76 evidence-based leadership competencies for new graduates and licensed PTs. 3 The panel reached consensus on 37 competencies as “very important” for new graduates and 20 competencies as “very important” for licensed PTs.…”
Section: Background and Purposementioning
confidence: 99%
“…3 The panel reached consensus on 37 competencies as “very important” for new graduates and 20 competencies as “very important” for licensed PTs. The framework 9 includes 57 competencies grouped into 11 clusters and 3 tiers (leadership of self, others, and organizations/communities). This framework was published after the UAB DPT program began implementation of the personal leadership curricular thread and is currently being validated.…”
Section: Background and Purposementioning
confidence: 99%

Leadership and physiotherapy: A scoping review

Ferrando-Margelí,
Suárez-Serrano,
Garay-Sanchez
et al. 2024
Heliyon